2006
DOI: 10.1046/j.1360-0443.1995.901114553.x
|View full text |Cite
|
Sign up to set email alerts
|

The economic costs of alcohol-related absenteeism and reduced productivity among the working population of New Zealand

Abstract: Lost productivity accounts for a significant proportion of the total cost of alcohol. This study quantifies the costs associated with alcohol consumption using survey data collected from four alcohol surveys conducted in Auckland between November 1990 to May 1992. The total sample size was 4662, of which 2638 were drinkers in paid employment. A computer-assisted telephone interviewing system was used to interview a random sample that closely matched the Auckland population. Respondents gave information about t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 8 publications
0
24
1
Order By: Relevance
“…More specifically, these studies propose that a higher level of modal alcohol consumption has an adverse impact on employee health which in turn increases the probability and/or duration of workplace absence. Indeed, research has consistently shown that excessive drinking over time increases the risk of a wide variety of chronic health problems including liver, musculoskeletal and cardiovascular problems (Hanebuth, Meinel, & Fischer, 2006; Jones, Casswell, & Zhang, 1995). Moreover, the incidence and severity of such chronic health problems have been directly associated with the level of employee sickness absence (Gmel & Rehm, 2003; Jones et al, 1995).…”
Section: Alcohol Use and Workplace Absenteeism: Main Effectsmentioning
confidence: 99%
“…More specifically, these studies propose that a higher level of modal alcohol consumption has an adverse impact on employee health which in turn increases the probability and/or duration of workplace absence. Indeed, research has consistently shown that excessive drinking over time increases the risk of a wide variety of chronic health problems including liver, musculoskeletal and cardiovascular problems (Hanebuth, Meinel, & Fischer, 2006; Jones, Casswell, & Zhang, 1995). Moreover, the incidence and severity of such chronic health problems have been directly associated with the level of employee sickness absence (Gmel & Rehm, 2003; Jones et al, 1995).…”
Section: Alcohol Use and Workplace Absenteeism: Main Effectsmentioning
confidence: 99%
“…Along with society, the addict and his or her family also suffer because substance abuse, dependence, and addiction are associated with an apparent devaluation of, and inattention to, natural rewards. Indeed, according to the DSM-IV, substance abuse and dependence involve a failure to fulfill major obligations at work, school, or home, the giving up of important social, occupational, or recreational activities, and continued drug use in spite of recurrent physical, legal, social, or psychological problems (American Psychiatric Association, 2000; Goldstein et al, 2007; Jones, Casswell, & Zhang, 1995; Nair et al, 1997; Santolaria-Fernandez et al, 1995). …”
mentioning
confidence: 99%
“…Although progress has been made in understanding the effects of ΔFosB in numerous aspects of drug addiction, one area that has not been investigated is the effect of ΔFosB on drug-induced devaluation of natural rewards. In humans, this phenomenon is manifested in reduced motivation for work, friends, family, and monetary gain (e.g., Goldstein et al, 2006, 2008; Jones, Casswell, & Zhang, 1995; Nair et al, 1997; Santolaria-Fernandez et al, 1995). …”
mentioning
confidence: 99%